Effects of a low carbohydrate diet on Obesity among Healthcare workers at Sukhothai hospital - Kunkitikad, Kanyakamon (Journal of Health Sciences Sukhothai hospital, 2026)
Background: from the annual health examination in 2023 at Sukhothai Hospital, healthcare workers with a body mass index (BMI) greater than 25 kg/m² about 43%. Low carbohydrate diet Program help to lose weight, decrease HbA1C and lipid level. Objective: This quasi-experimental study with a two-group pretest–posttest design aimed to examine the effects of a low-carbohydrate diet on body weight, waist circumference, body fat composition, and lipid profiles among obese healthcare personnel at Sukhothai Hospital. Methods: The participants consisted of 95 healthcare workers with a body mass index (BMI) greater than 25 kg/m², identified from the annual health examination in 2023. Participants were voluntarily recruited without randomization and subsequently allocated into an experimental group (n=49) and a control group (n= 46) based on preference. Baseline assessments, including body weight, anthropometric measurements, and lipid profiles, were conducted during the first week following obesity education for all participants. The experimental group received a low-carbohydrate dietary program (60–130 g/day), combined with multidisciplinary support, application-based monitoring, and continuous health education. The control group maintained their usual dietary patterns. Outcome measures were reassessed after 12 weeks. Statistical analyses included Chi-square test and independent-sample t test for between-group comparisons, and paired-sample t test for within-group comparisons. Results: After 12 weeks, the experimental group demonstrated significantly lower triglyceride levels compared to the control group (p < 0.05). Significant reductions were observed in body weight, waist circumference, visceral fat, and triglyceride levels compared to baseline (p < 0.05). However, no difference in body weight was found between the two groups (p > 0.05), which may reflect suboptimal adherence to dietary recommendations among healthcare personnel with high workload demands. Conclusion: Future health promotion programs should adopt a multidisciplinary approach to enhance adherence and achieve sustainable weight management outcomes.